Investigation on types of corn rust in eastern Yunnan ecology and analysis of population genetic structure of its rusts. (31st December 2022) - Wenqiang, Zhu; Jingran, Wang; Qi, Wu; Na, Wang; Jianwei, Guo; Zilin, Yang; Yun, Sha; Lin, Liu; Chengyun, Li
ABSTRACT: Corn rust disease can be classified into four types: common corn rust, southern corn rust, tropical corn rust and stem corn rust. In this paper, 270 samples of corn rust gathered from Yunnan province were identified by observation of symptom and pathogen morphology, detection of specific molecular markers between Puccinia sorghi Schw and Puccinia polysora Unedrw. The results showed that 180 samples of corn rust collected form Qujing, Zhaotong, Kunming, Honghe (Mile, Kaiyuan and Jianshui) were common corn rust caused by Puccinia sorghi Schw; and 90 samples of corn rust collected form Wenshan and Honghe (Pinbian) were southern corn rust. Morphology and aspect ratio compared Puccinia sorghi Schw with Puccinia polysora Unedrw. The uredospores of Puccinia polysora Unedrw were oval and the aspect ratio of 81.6% of all uredospores from Puccinia polysora Unedrw was greater than 1.2. The uredospores of Puccinia sorghi Schw were nearly round, and their aspect ratio was 1.0-1.3. In addition, the population genetic structure of all corn rust samples was analyzed by ISSR molecular marker. Concerning Puccinia polysora Unedrw, the genetic diversity was larger in Wenshan than in Honghe. In Puccinia sorghi Schw, the population genetic diversity was larger in Zhaotong and the lowest in Kunming.